Menumbuhkan Kreativitas dalam Matematika: Analisis Sistematis Kemampuan Berpikir Kreatif Matematis dan Faktor Afektif yang Mempengaruhinya - Jaelani Sidik; Meiliasari Meiliasari; Wardani Rahayu (Universitas Cokroaminoto Palopo, 2025)
This study aims to conduct a systematic review of mathematical creative thinking abilities and the affective factors that influence them based on national and international research findings. This study will piece together the pieces of the “puzzle” into a comprehensive big picture, resulting in evidence-based and theoretically sound recommendations. This study uses the Systematic Literature Review (SLR) method with a descriptive analytical approach to empirical articles published between 2020 and 2025 in accredited national journals and reputable international journals. The results of the analysis show that mathematical creative thinking skills, which include indicators of fluency, flexibility, originality, and detail of ideas, have improved through the application of innovative and student-centered learning models, such as Creative Problem Solving, Project-Based Learning, SAVI, the Lesson Study-based Problem Solving model, and the Indonesian Realistic Mathematics Education approach. In addition to learning strategies, a number of affective factors such as self-efficacy, self-regulated learning, motivation, perception of creativity, and learning style were found to contribute positively to the development of mathematical creativity. Conversely, mathematical anxiety was found to be an inhibiting factor that reduced flexibility and fluency of thinking. Additional findings also showed that computational thinking and perception of creativity played an important mediating role in the relationship between self-confidence and mathematical creative thinking skills. Overall, the study results emphasize the importance of a holistic approach that combines pedagogical innovation with strengthening students' affective aspects in an effort to develop mathematical creative thinking skills. Educators should not only focus on technical pedagogical training for teachers, but also provide guidance on managing students' psychological aspects. The synergy between innovative teaching methods and an emotionally supportive learning environment will be a major factor in producing a generation that is mathematically competent and creative.